Effects of oxytetracycline and flunixin meglumine treatments on the haematological and serum biochemistry profiles of goats experimentally induced with Mannheimia haemolytica Pneumonia - Abdul Hamid, Fathin Faahimaah; Hanif Reduan, Mohd Farhan; Sabri, Jasni; Abdullah, Faez Firdaus Jesse; Naji Odhah, Mohammed; Abdul Manaf, Nur Athirah; Norsidin, Mohd Jefri; Che Yahya, Siti Nor; Kamaruzaman, Intan Noor Aina; Mohd Rajdi, Nur Zul Izzati (Nexus Academic Publishers, 2023)
Mannheimiosis is one of the common causes of pneumonia caused by Mannheimia haemolytica. Evaluation of the hematological and serum biochemistry changes is critical to determine the effectiveness of the treatment approach in reducing the severity of infection. Healthy goats (n=20) were equally divided into 5 groups: Mannheimia haemolytica 107 concentration was inoculated intranasally to all goats except goats of Group 1 which served as the negative control, Group 2 was the positive control, Group 3 goats treated with oxytetracycline, Group 4 goats were treated with flunixin meglumine, and group 5 received both oxytetracycline and flunixin meglumine treatments. Blood samples were collected at 24 hours, days 5, 7, 9, 11, 14, 21, and 28 post-inoculation for the clinical pathology evaluation through complete blood count and serum biochemistry evaluation. Results showed that post-infection resulted mild fluctuation of the red blood cell parameters in the goats with a decrease in the total white blood cell count (p<0.05). The serum biochemistry shows the total protein, albumin and globulin are within the range with mild increment in creatine kinase, blood urea nitrogen, and gamma glutaryl transferase however there were increased lactate dehydrogenase levels post-infection with Mannheimia haemolytica (p<0.05). In conclusion, oxytetracycline and flunixin meglumine treatments does not have a great influence on the parameters evaluated in goats experimentally induced with Mannheimia haemolytica pneumonia.